Potential Of Aduncum Leaf Essential Oils (Piper aduncum L) As An Antibacterial For Dental Caries - Aryani, Farida; Arensyah, Mardy; Hernandi, Muhammad Fikri; Hertianti, Erina; Wartomo, Wartomo; Prayitno, Joko; Yusuf, Andi; Zarta, Abdul Rasyid; Sari, Nur Maulida (Politeknik Pertanian Negeri Samarinda, 2024)
Aduncum leaf (Piper aduncum L) have the potential as antifungal from phenolic compounds and their derivatives. Essential oils have been widely used by the community both for health, this is because of the compound content that is known to be used as antibacterial. This study aims to determine the physical properties and antibacterial activity of the aduncum leaf essential oil (Piper aduncum L). Distillation is carried out using a steam and water distillation method. Testing physical properties include color, type weight using a pycnometer and refractive index using a refractometer. Antibacterial testing is carried out by diffusion method so that the wells with modification using Streptococcus sobrinus and Streptococcus mutants. Chloramphenicol is used as a positive control in antibacterial testing. The results of testing physical properties showed the essential oil of the aduncum leaf with the M1 code had an oil weight of 6.75 gr golden yellow with a weight type 0.97875 and the Bias Index of 1,508. Oil with the M2 code has an oil weight of 3.34 gr in yellow brown with a weight of 1,01635 and a refractive index of 1,512. The results of testing the antibacterial activity S. sobrinus showed the diameter of the inhibition of aduncum leaf essential oil included in the moderate category with a value of around 6 mm-12 mm, while S. mutans antibacterial activity shows the diameter of inhibiting aduncum leaf essential oil included in the moderate category with a value of around 8 mm-15 mm. Based on the results of the study obtained, the essential oil of the aduncum leaf can be recommended as an antibacterial caries and can be developed.